A survey on developing publish/subscribe middleware over wireless sensor/actuator networks - Sheltami, Tarek R.; Al-Roubaiey, Anas A.; Mahmoud, Ashraf S. Hasan (Wireless networks, 2016)
Publish/subscribe (Pub/Sub) interaction paradigm is receiving more attention in commercial and academic research nowadays. It is an effective interaction scheme for large-scale distributed systems due to its ability of decoupling communicating entities in time, space, and synchronization. The decoupling properties are well-suited for Wireless Sensor Network (WSN) applications because of their special characteristics such as data-centricity, dynamicity, and many-to-many communications. Many studies have been conducted to adapt Pub/Sub communication model to WSN. In this paper, we review the Pub/Sub interaction paradigm in the context of WSN. Moreover, we classify, analyze and synthesize different Pub/Sub based solutions proposed recently for WSN and discuss the open problems and new research directions in this area. Also, we propose a new reference model for pub/sub middleware in wireless sensor and actuator networks. To the best of our knowledge this is the first survey on this specific subject.